Sistem Informasi Akuntansi Manajemen, Orientasi Pasar dan Kinerja UMKM: Peran Mediasi Kemampuan Inovasi - Susetyo, Aris; Suliyanto, Suliyanto; Susilowati, Dewi; Herwiyanti, Eliada; Lestari, Puji (Politeknik Ganesha Medan, 2024)
Performance is a combination of strategic, administrative and operational management of an organization. To become superior MSMEs, able to compete and be sustainable in the future, it is necessary to master management accounting information systems, understand market orientation and innovation capabilities, which are a must for MSMEs to master. The aim of this research is to determine the influence of management accounting systems, market orientation on performance and innovation capabilities as mediating variables on MSME information actors. A total of 295 MSMEs in the food and beverage sector were studied. Data collection used a questionnaire with purposive sampling technique. The results of this study support the research hypothesis. Management accounting information systems, market orientation, innovation capabilities have a positive effect on performance. Innovation capability can mediate the influence of management accounting information systems on performance, and innovation capability also mediates the influence of market orientation on performance. The theoretical contribution of research is that management accounting information systems can be explained by the theory of the superiority of human resource-based competencies on performance, because management accounting information systems can support organizations in creating competitive advantages. Empirical findings that innovation capabilities can mediate management information systems to performance and innovation capabilities can mediate market orientation to performance.